The Main Directions for Improving the Efficiency of the Enterprise - Bakhodirovna, Kurbanova Sitora (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
The article considers the main directions of increasing the efficiency of the enterprise. The article also provides several tools that make it possible to increase the efficiency of the enterprise.